Developing a Williams' Indicators-Based Assessment Rubric for Measuring Students' Multiple Creativity in Green Chemistry Learning through the C-R-E-A-T-E Model - Wahyu, Wawan; Oktiani, Rosi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study developed and validated a Williams' indicators-based assessment rubric for measuring senior high school students' multiple creativity in Green Chemistry learning through the C-R-E-A-T-E model. The study used an educational research and development design organized through the ADDIE procedure. The validation phase involved five experts, comprising three assessment specialists and two chemistry education/content specialists, while limited classroom implementation involved 20 Grade XII science students and one chemistry teacher in Bandung, Indonesia. The product was designed to evaluate creative outputs in several modalities, including audio, visual, audiovisual, written-digital, and kinesthetic products, using five Williams' creativity indicators: fluency, flexibility, originality, elaboration, and evaluation. Data were collected through curriculum and needs analysis, expert validation sheets, implementation notes, and descriptive percentage analysis. The assessment rubric obtained an average expert validation score of 89.16%, whereas the supporting Green Chemistry material obtained 88.00%, indicating that both components were valid and feasible for limited classroom use after revision. Rubric validation was strongest for fluency, flexibility, and originality, while elaboration and evaluation required more explicit descriptors and exemplars. The findings indicate that the rubric can help chemistry teachers shift from conventional achievement-focused assessment toward more authentic, multidimensional, and criteria-based creativity assessment. Further multi-school validation and inter-rater reliability testing are required before large-scale implementation.